The CDIO-FCDI-FFCD Rubrics for Evaluation of Three-Cycle Engineering Programs - A. I. Chuchalin (Высшее образование в России)
The aim of the paper is to propose Rubrics for self-evaluation of graduate and postgraduate engineering programs based on the FCDI (Forecast, Conceive, Design, Implement) Standards and FFCD (Foresight, Forecast, Conceive, Design) Standards by analogy with Rubrics for self-evaluation of undergraduate engineering programs based on the CDIO (Conceive, Design, Implement, Operate) Standards. The FCDI Standards and FFCD Standards were developed for Master’s and Doctoral engineering programs as a result of the CDIO approach evolution and by analogy with the CDIO Standards originally developed for Bachelor’s engineering programs. The CDIO/FCDI/FFCD Standards are recommended for the design and implementation of three-cycle engineering programs to train graduates for complex, innovative and research engineering activities, respectively, taking into account the features of the division of labor in the engineering profession. The 6-level scale Rubrics are helpful for evaluation the degree of Bachelor’s, Master’s and Doctoral engineering programs compliance with the recommendations of the CDIO, FCDI and FFCD Standards, respectively.